ABOUT THE WISDOM OF AHMAD YASSAWI: https://doi.org/10.5281/zenodo.15470017 - Mukhammadiyeva, Sayyora (Journal of Contemporary World Studies, 2025)
This article discusses the historical roots of education, the ideas put forward in research on the problems of spiritual and moral education in our country, in particular, the importance of the humanitarian ideas of Hodja Ahmad Yassavi in the education of young people today.